Powdered activated carbon addition for fouling control in anaerobic membrane bioreactor. (September 2021) - Sohn, Weonjung; Guo, Wenshan; Ngo, Huu Hao; Deng, Lijuan; Cheng, Dongle
Abstract: The effect of powdered activated carbon (PAC) addition to a conventional anaerobic membrane bioreactor (AnMBR) on removal performance and membrane fouling was explored in this study. The optimal one-off PAC dose could increase average chemical oxygen demand (COD) and total organic carbon (TOC) removal rates up to 15.7% and 15.6%, respectively. The PAC addition exhibited not only lower TMP increase rate, but also reduced soluble microbial product (SMP) and extracellular polymeric substances (EPS). Higher protein to polysaccharide ratio of SMP and higher zeta potential in AnMBR with PAC could enhance hydrophobicity and flocculation ability, thereby effectively alleviating membrane fouling. Lower total membrane resistance and pore blocking resistance indicated that PAC addition could prevent both severe pore blocking and irreversible fouling, due to the lower polysaccharide level in SMP of the cake layer. Moreover, PAC addition facilitated the decrease in fouling-related bacteria such as Cloacibacterium and Paludibacter . Graphical abstract: Unlabelled Image Highlights: PAC addition could increase nutrient, COD as well as TOC removal efficiencies. Increase of zeta potential and SMPp enhanced hydrophobicity of sludge. PAC effectively mitigated pore blocking and irreversible fouling. PAC addition facilitated less enrichment of fouling-associated microorganisms.